Obtenção de pós de tântalo metálico a partir da redução aluminotérmica com ignição a plasma - Brito, Roseane Aparecida de (2007)
Metallic tantalum has a high commercial value due to intrinsic properties like excellent ductility, corrosion resistance, high melt and boiling points and good electrical and thermal conductivities. Nowadays, it is mostly used in the manufacture of capacitors, due to excellent dielectric properties of its oxides. In the nature, tantalum occurs in the form of oxide and it is extracted mainly from tantalite-columbite ores. The tantalum is usually produced by the reduction of its oxide, using reductants like carbon, silicon, calcium, magnesium and aluminum. Among these techniques, the aluminothermic reduction has been used as the industrial method to produce niobium, tantalum and their alloys, due to the easy removal of the Al and Al2O3 of the system, easing further refining. In conventional aluminothermic reduction an electrical resistance is used to trigger the reaction. This reaction self-propagates for all the volume of material. In this work, we have developed a novel technique of aluminothermic reduction that uses the hydrogen plasma to trigger the reaction. The results obtained by XRD, SEM and EDS show that is possible to obtain a compound rich in tantalum through this technique of aluminothermic reduction in the plasma reactor